HOUSEHOLD WATER QUALITY CHALLENGES AND CONTAMINATION RISKS IN INFORMAL SETTLEMENTS OF A DEVELOPING COUNTRY: A CASE STUDY IN DAR ES SALAAM CITY, TANZANIA (The Journal of Building and Land Development, 2023)
Sanitation and hygiene practices are inadequate for household water quality protection in informal settlements of developing countries. Household water is at contamination risk and could result into waterborne diseases. Most of previous studies focused on the impacts of quality of water sources in informal settlements. This study focuses on household water quality and contamination risks in informal settlements in developing countries. Physical observations, structured interview and laboratory analysis were deployed for data collection. 180 households were interviewed. Additionally, 28water samples were analyzed in the laboratory following the standard methods. Results showed that 36.7% of households at Mogo-Majumbasita, Dar es Salaam have in-house water supply connections. The rest depends on water fetched from kiosks. It was found that total coliforms increased from 4 counts/100 ml at main sources to 42 counts/100 ml at households’ storage water facility, while fecal coliforms increased from 3 counts/100 ml to 28 counts/100 ml. This study revealed that there is recontamination of water stored in the household. The contamination is associated with unsatisfactory hygiene of domestic water storage facilities, unhygienic condition of the storage cover and vessels that are used to draw water from the water storage. Household water should be kept clean and safe for human consumption.